Long‐term lower urinary tract sequelae following AUS cuff erosion. Issue 1 (24th September 2021) - Chertack, Nathan A.; Caldwell, Kelly M.; Joice, Gregory A.; Kavoussi, Mehraban; Dropkin, Benjamin M.; Ortiz, Nicolas M.; Baumgarten, Adam S.; Shakir, Nabeel A.; Sanders, Sarah C.; Hudak, Steven J.; Morey, Allen F.
Abstract: Aims: To examine the rate of lower urinary tract complications (LUTC) and urinary diversion (UD) after artificial urinary sphincter (AUS) explantation with the acute reconstruction of AUS cuff erosion defects. Methods: We performed a retrospective study of patients who underwent in‐situ urethroplasty (ISU) for AUS cuff erosion from June 2007 to December 2020. Outcomes included LUTC (urethral stricture, diverticulum, fistula), AUS reimplantation, and UD. Defect size was prospectively estimated acutely and a subanalysis was performed to determine the impact of erosion severity (small erosions [<33% circumferential defect] and large erosions [≥33%]) on these outcomes. Kaplan–Meier curves were created to compare survival between the two groups. Results: A total of 40 patients underwent ISU for urethral cuff erosion. The median patient age was 76 years old with a median erosion circumference of 46%. The overall LUTC rate was 30% (12/40) with 35% (14/40) of patients requiring permanent UD. Secondary AUS placement occurred in 24/40 (60%) patients with 11/24 (46%) leading to repeat erosion. On subanalysis, small erosion was associated with improved LUTC‐free and UD‐free survival but not associated with AUS reimplantation. Conclusions: Lower urinary tract complications are common after AUS cuff erosion and can lead to the need for permanent UD. Patients with larger erosions are more likely to undergo UD and reach this end‐stage condition earlier compared to patients with small erosions.